Debts, Differently: Alternative Finance Organizations in Italy and France - Lovera, Arianna (PARTECIPAZIONE E CONFLITTO, 2015)
The main purpose of this article is to analyze the possibility of implementing financial practices that, in the principles that guide them, are different from and question the functioning of most banks in capitalist societies. In particular, the article describes the ways in which credit relationships (i.e. relationships between credit institutions and their borrowers) are conceived and shaped by some “alternative” banks and financial cooperatives. The findings are based on ethnographic fieldwork, including observations and in-depth interviews, focused on three financial organizations: Banca Etica (Italy), MAG6 (Italy), and La Nef (France). While striving to establish “another kind of finance”, different from the capitalistic, speculative form, these banks and financial cooperatives aim to create more cooperative and solidarity-based credit relationships.